Decision Making Method Related to Pythagorean Neutrosophic Hypersoft Sets - A. Francina Shalini, G. Ramya (Mathematical Statistician and Engineering Applications, 2022)
PNHSS is a new approach towards decision making under uncertainty. This study presents a new algorithm for group decision-making solutions using PNHSMs and confident weight is given by experts. PNHSS is deriving from the combination of Pythagorean Neutrosophic set and Hypersoft set. PNHSM is also the matrix representation of PNHSS. To demonstrate the validity of the proposed approach, a numerical example has been presented. The obtained results show that our developed approach is most effective.